Efficient power allocation in downlink multi‐cell multi‐user NOMA networks. Issue 4 (1st March 2019) - Khan, Wali Ullah; Yu, Zhiyuan; Yu, Shanshan; Sidhu, Guftaar Ahmad Sardar; Liu, Ju
Abstract : Recently, non‐orthogonal multiple access (NOMA) has been considered as a promising radio access technique for the upcoming fifth generation networks. In this study, the authors consider the downlink multi‐cell multi‐user cellular network, where the base station (BS) located in the centre of each cell intends to communicate with multiple random distributed user equipments (UEs) using NOMA protocol. They formulate an optimisation problem to increase the sum network capacity under various practical constraints. Especially, the transmission power budgets for BSs, power allocation for UEs, and minimum rate requirements per UE are optimised. Moreover, they obtain the optimal power allocation via local optimal solution iteratively, which satisfies Karush–Kuhn–Tucker conditions. The simulation results show that the proposed scheme can converge after few iterations and achieve higher sum capacity compared with the non‐optimal NOMA and orthogonal multiple access schemes.